A whole-genome sequence based association study on pork eating quality traits and cooking loss in a specially designed heterogeneous F6 pig population. (December 2018) - Ji, Jiuxiu; Zhou, Lisheng; Huang, Yizhong; Zheng, Min; Liu, Xianxian; Zhang, Yifeng; Huang, Cong; Peng, Song; Zeng, Qingjie; Zhong, Liepeng; Yang, Bin; Li, Wanbo; et al.
Abstract: To determine the genetic basis of pork eating quality traits and cooking loss, we herein performed a genome-wide association study (GWAS) for tenderness, juiciness, oiliness, umami, overall liking and cooking loss by using whole genome sequences of heterogeneous stock F6 pigs which were generated by crossing 4 typical western pig breeds (Duroc, Landrace, Large White and Pietrain) and 4 typical Asian pig breeds (Erhualian, Laiwu, Bamaxiang and Tibetan). We identified 50 associated loci (QTLs) and most of them are novel. Seven loci also showed pleiotropic associations with different traits. In addition, we identified multiple promising candidate genes for these traits, including PAK1 and AQP11 for cooking loss, EP300 for tenderness, SDK1 for juiciness, FITM2 and 5-linked MYH genes for oiliness, and TNNI2 and TNNT3 for overall liking. Our results provide not only a better understanding of the genetic basis for meat quality, but also a potential application in future breeding for these complex traits.